A Survey of Neonatal Nurses on Mydriatic Regimens Used in Neonatal Retinopathy of Prematurity Eye Examinations - Kremer, Lisa; Reith, David; Medlicott, Natalie J.; Sime, Mary J.; Edmonds, Liza; Broadbent, Roland (American Journal of Perinatology, 2021)
Objective This study was aimed to determine mydriatic regimen(s) used in neonatal units in Aotearoa, New Zealand (NZ), and Australia and to estimate the frequency of adverse drug events following mydriatic administration in preterm neonates.Study Design A cross-sectional survey was sent to neonatal nursing staff listed in the Australian and New Zealand Neonatal Network contact list. Participants were asked to state what mydriatic regimen they use, and to estimate the frequency of adverse drug events when eye drops were administered for retinopathy of prematurity eye examinations (ROPEE).Results Thirteen different mydriatic regimens were identified; phenylephrine 2.5% and cyclopentolate 0.5% (1 standard drop of each) was the most commonly used regimen. Two of the regimens exceeded adult doses and five regimens included a mydriatic that is equivalent to an adult dose. Following mydriatic instillation, the three most common adverse effects were apnea, tachycardia, and periorbital pallor.Conclusion Low-concentration single-microdrop regimens are currently in use and resulting in successful ROPEE, yet doses exceeding adult doses are in use throughout Aotearoa, NZ, and Australian units. We know from this dataset that neonates are experiencing unwanted and potentially preventable, adverse effects associated with mydriatics, and every effort should be made to minimize this risk.Key Points
Keywords: retinopathy; neonate; mydriatic; phenylephrine; cyclopentolate; tropicamide; adverse drug event